2023
DOI: 10.1097/shk.0000000000002226
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Model Derived From Analysis of Time-Course Gene-Expression Datasets Reveals Temporally Stable Gene Markers Predictive of Sepsis Mortality

Min Huang,
Mihir R. Atreya,
Andre Holder
et al.

Abstract: Sepsis is associated with significant mortality and morbidity among critically ill patients admitted to intensive care units (ICU) and represents a major health challenge globally. Given the significant clinical and biological heterogeneity among patients and the dynamic nature of the host immune response, identifying those at high risk of poor outcomes remains a critical challenge. Here, we performed secondary analysis of publicly available time-series gene-expression datasets from peripheral blood of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…At the genetic level, there have also been some breakthroughs in explaining different sepsis prognoses. Huang et al (23) revealed seven potential genetic biomarkers for predicting sepsis mortality through a machine learning model. Kapp et al (24) discovered information regarding molecular factors that may help explain the differences in sepsis survival outcomes among African American/Black and non-Hispanic White patients with primary urinary tract infection.…”
Section: Discussionmentioning
confidence: 99%
“…At the genetic level, there have also been some breakthroughs in explaining different sepsis prognoses. Huang et al (23) revealed seven potential genetic biomarkers for predicting sepsis mortality through a machine learning model. Kapp et al (24) discovered information regarding molecular factors that may help explain the differences in sepsis survival outcomes among African American/Black and non-Hispanic White patients with primary urinary tract infection.…”
Section: Discussionmentioning
confidence: 99%
“…ML has shown great promise in enhancing the prediction, diagnosis, and management of sepsis. Min Huang et al conducted the Support Vector Machine classifier and identified mortality biomarkers of sepsis (16). Moreover, another study applied a new machine learning method in predicting 20 differentially expressed genes for sepsis outcomes (17).…”
Section: Discussionmentioning
confidence: 99%